2004
DOI: 10.1097/00002341-200405000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin Type A for Dysthyroid Upper Eyelid Retraction

Abstract: : Botulinum toxin type A may be used in the inflammatory stage of thyroid eye disease to improve upper eyelid retraction. Individual response to treatment is variable, but this modality should be considered as a temporizing measure until stability for surgery is reached.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
12

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 10 publications
3
42
0
12
Order By: Relevance
“…The current investigation confirms several previous studies reporting favourable results with BTA in the treatment of ULR 3,6,8,10,13,14 and suggests that BTA may come to play an important role in the management of ULR secondary to TED. Considering the lack of treatment options for congestive-stage ULR, the long preoperative waiting time and the often unpredictable results of surgical treatment (including the frequent occurrence of abnormalities in lid contour) in the fibroticstage, the addition of a relatively simple treatment option such as BTA injection is a welcome initiative.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The current investigation confirms several previous studies reporting favourable results with BTA in the treatment of ULR 3,6,8,10,13,14 and suggests that BTA may come to play an important role in the management of ULR secondary to TED. Considering the lack of treatment options for congestive-stage ULR, the long preoperative waiting time and the often unpredictable results of surgical treatment (including the frequent occurrence of abnormalities in lid contour) in the fibroticstage, the addition of a relatively simple treatment option such as BTA injection is a welcome initiative.…”
Section: Discussionsupporting
confidence: 91%
“…Dintelman et al, 13 evaluated 13 patients with ULR after injection of 5-15 units of Botox and reported that eight patients were satisfied with the results. On the other hand, Morgenstern et al, 14 were the first to evaluate a series of patients with TED in the congestive stage. A mean reduction of 2.35 mm was observed 1 week after injection of BTA in 18 patients.…”
Section: Introductionmentioning
confidence: 99%
“…This very rarely gives rise to severe or prolonged ptosis, and we have not encountered BoNTA-induced hypotropia or superior rectus underaction; a finding consistent with studies that have utilised even larger subconjunctival doses. 4,5 Topical local anaesthetic is instilled and the upper eyelid is everted. A minimum dose of 2.5 units and maximum of 7.5 units (usual dose 5 units for scleral show 1-2 mm) BoNTA (Botox diluted 5 units/0.1 ml, Allergan Limited, UK) is administered via a single injection into the subconjunctival space at the superior margin of the central tarsal plate.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…A TBA, ao agir relaxando o músculo estriado (MLPS), poderia evitar a "contratura inflamatória", prevenindo a fibrose e subseqüente encurtamento muscular (11) . No entanto, seria necessário o seguimento dos pacientes por maior período de tempo -além de uma comprovação histológica -para determinar se a TBA é real-mente capaz de impedir a fibrose no MLPS a longo prazo, caso fosse aplicada nos pacientes no estágio inicial da doença.…”
Section: Discussionunclassified
“…Na literatura pesquisada, a TBA reduziu a retração palpebral em 2 a 6 mm e seu efeito durou 1 a 6 meses (5)(6)(7)(8)(9)(10) . Em 2004, Morgenstern et al (11) sugeriram o uso da TBA no tratamento de pacientes com retração palpebral na fase aguda da OD. No entanto, neste estudo, a administração da TBA foi via transconjuntival e não foi apresentado o seguimento clíni-co, mas, apenas, o resultado imediato após a aplicação.…”
Section: Resumo Introduçãounclassified